Al-Azhar’s approach to tajdīd: a case study of fiqh textbooks - Omara, Attia; Abdelaziz, Berghout (IIUM Press, 2025)
Pre-university Islamic Education in Egypt is provided through Al-Azhar Institutes where more than 2 million students are enrolled today. Since its establishment, Al-Azhar Institutes have gone through various changes with regards to the length of the study period and its educational curriculum. This study focuses on the most recent modifications in al-Azhar Institutes’ fiqh curriculum introduced in 2013, after the outbreak of the Arab Spring. In the aftermath of the Arab Spring, Al-Azhar faced accusations of teaching classical books that include ideas that promote extremism and preach a sectarian divide. This was followed by the authoring of a “simplified” version of the fiqh textbooks instead of the classical fiqh textbooks. Hence, this study seeks to answer the following questions: What is the nature of these modifications in the fiqh curriculum? Was it for ideological or pedagogical reasons? Is it a state sponsored project or ʿulamā led effort? Using content analysis and comparative methods, the study analyzes and compares the “simplified” textbooks with the “original” textbooks to identify the patterns of changes and to outline the nature of the modifications and hence the reasons behind it. The analysis shows that one of the main purposes for the modification is to simplify the textbooks and to make them age appropriate for middle and secondary school students. The modification was conducted in accordance with the ʿulamā’s conceptualization of the revival (tajdīd) that Islam needs, a revival that preserves the authenticity of the Islamic tradition (turāth).